(3TQM CHjGJ GdeaUds - (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s; (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s
(3ChdgG (B:s
(3hHYO, abO SfM dj, HYO eG GdJeS efj ENhGfj ef ebJHS GdYde Cf CcJH Ydi eG CNHQ Hg s
(3BNQgG (B:s
(3GdGSJTgGO Ydi Cf bhdg(B: (3YdeGA CUdg Ydi GdeGA Ydi Cfg LGQ heLQhQ, hPdc dZI ajg Je s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3hHYV GdWjGQGJs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B178 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B186 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B402s
Keywords: (3GdfMhs